High-dose rate intraluminal brachytherapy: An effective palliation for cholangiocarcinoma causing bile duct obstruction. (December 2018) - Nguyen, Nhu-Tram A.; Timotin, Emilia; Hunter, Robert; Sur, Ranjan K.
Highlights: Intraluminal brachytherapy (ILBT) decreases the need for biliary drain changes. Post-ILBT, the median number of drain changes was 0 (range 0–4). Post ILBT, the 30-day and 60-day patency rates were 88% and 83% respectively. Most patients had a biochemical response; many had their bilirubin normalized.